Nanoscale Surface Deformation of the Granular Со₂₅Ag₇₅ Films - Gorobets, O.Yu.; Yakymenko, Yu.I.; Kravets, A.F.; Brukva, O.M.; Zakharchenko, V.N.; Mikhalko, S.V.; Sizon, I.A. (Металлофизика и новейшие технологии, 2015)
Granular nanostructure Со₂₅Ag₇₅ films are analysed by means of the scanning tunnelling microscopy (STM) method. The phenomenon of giant film nanodeformation is detected with the 10% change of average height during the initial magnetization of the sample and with the 2% change after 8 days of relaxation during secondary magnetic field action. The changing of the shape of nanoscale granules and their displacement in the surface of film are observed during the process of nanodeformation under the action of magnetic field and in the aftereffect processes. Методою тунельної мікроскопії досліджено вплив магнетного поля на плівки ґранульованих наноструктур Со₂₅Ag₇₅. Було виявлено ефект гігантської нанодеформації з 10% зміною середньої висоти зразка впродовж первинного намагнетування і 2% зміною після 8 днів релаксації під час повторного намагнетування. Зафіксоване явище пов’язане із деформацією магнетних ґранул та їх зміщенням у немагнетній матриці під дією магнетного поля. Методом туннельной микроскопии исследовано влияние магнитного поля на плёнки гранулированных наноструктур Со₂₅Ag₇₅. Был обнаружен эффект гигантской нанодеформации с 10% изменением средней высоты поверхности образца в течение первичного намагничивания и 2% изменением после 8 дней релаксации во время повторного намагничивания. Зафиксированное явление связано с деформацией магнитных гранул и их смещением в немагнитной матрице под действием магнитного поля.